Risk Factors for High and Low Placental Weight. Issue 2 (20th December 2013) - McNamara, Helen; Hutcheon, Jennifer A.; Platt, Robert W.; Benjamin, Alice; Kramer, Michael S.
Abstract Background Placental weight is an independent predictor of adverse perinatal outcome. However, risk factors for high and low placental weight are poorly understood. The objective of this study was to identify maternal, placental, and umbilical cord determinants of placental weight, before and after accounting for birthweight. Methods This cohort study of 87 600 singleton births at the Royal Victoria Hospital in Montreal, Canada assessed the relationship between maternal, placental, and umbilical cord characteristics and placental weight (standardised for sex and gestational age). We separately examined risk factors for high (z‐score >+1) and low (z‐score <−1) placental weight. Multivariable logistic regression was used to study associations after adjusting for confounders and further adjusting for birthweight. Results Chronic hypertension was associated with low placental weight {relative risk (RR) 2.1 [95% confidence interval (CI) 1.8, 2.4] and 1.8 [95% CI 1.5, 2.1] before and after accounting for birthweight}, while pre‐eclampsia was associated with low placenta weight before, but not after adjustment for birthweight. Anaemia and gestational diabetes were linked with high placental weight (RRs 1.2–1.4, respectively) before and after adjustment for birthweight, while smoking was linked with high placental weight only after adjustment for birthweight (RR 1.4 [95% CI 1.3, 1.5]). Placental and cord determinants of high placental weight included chorioamnionitis, chorangioma/chorangiosis, circumvallate placenta, marginal cord insertion, and other cord abnormalities. Conclusions The broad range of risk factors for high placental weight suggests multiple aetiologic pathways. Future work should seek to understand the pathways by which the placenta adapts to unfavourable intrauterine conditions, which may provide insights into potential therapies.